Formation and Uses of Imidazo[1,2-a]pyrimidines and Related Compounds: A Review Comprising Years 2000-2021 - Kobak, Rabia Zeynep; Akkurt, Barbaros (The Turkish Chemical Society, 2022)
This work covers the selected synthetic papers of imidazo[1,2-a]pyrimidine and its derivatives between the years 2000 and 2021. Synthesis of the heterocyclic moiety, application of this scaffold to biological activities, and secondary applications like corrosion inhibition are provided. The authors hope that readers will find the treatise useful.
Keywords: Inorganic Chemistry; İnorganik Kimya; Imidazo[1; a]pyrimidine; synthesis; biological applications; uses